Pathogenicity of Stable L-Phase Variants of Staphylococcus aureus: Failure to Colonize Experimental Endocarditis in Rabbits - Linnemann, Calvin C. (1973)
Endocarditis was induced in the rabbit by the placement of a polyethylene catheter in the right heart. The catheter was filled with stable L-phase variants of Staphylococcus aureus to determine if the variant form would colonize the damaged endocardium and produce further tissue injury similar to that produced by the vegetative bacterial phase. No L-phase variants were recovered from cultures of blood or vegetations, although pure cultures of L-phase variants were obtained from all catheters, including one in place for 70 days. The vegetations were grossly similar in control animals with sterile media in the catheters and animals with catheters containing L-phase variants, although polymorphonuclear leukocytes and eosinophils were more frequently found in vegetations from animals inoculated with L-phase variants. Endocarditis was also induced in animals with vegetative S. aureus and then treated with penicillin G. Blood cultures in hypertonic media often grew vegetative S. aureus when there was no growth in routine media, but no L-phase variants were detected. Vegetative S. aureus, but not wall-defective variants, were isolated from vegetations of all treated animals.